(untitled) (Scientific journal of the Fergana State University, 2023)
The authors of this study set themselves the task of developing a synergistic concept of pedagogical diagnostics of conflict behavior of students of higher educational institutions. The sequence of four substructures is described according to the concept of the dynamic structure of personality, their meaning and their inherent dependence of the occurrence of conflicts on these substructures. Conflict behavior in the educational process, conflicting parties, their interaction, the possibility of preventing conflicts and mitigating conflict situations, in addition, the importance of objectivity in their elimination, conflict studies are studied as an integral system. The study analyzed the synergistic, theoretical foundations of conflicts based on various theories and concepts based on the interpretation of conflicts in the social environment of higher education, such as a macro-social approach, as well as the possibility of successfully organizing the pedagogical activity of the process of educating the younger generation as a perfect personality in educational institutions, practical recommendations for the prevention and elimination of pedagogical disputes have been developed. As a result of pedagogical diagnostics of students’ behavior in conflict situations that arise between university students, a synergistic model of conflict resolution has been developed.